Understanding Dendritic Cells and Their Role in Cutaneous Carcinoma and Cancer Immunotherapy - Valerie R. Yanofsky; Hiroshi Mitsui; Diane Felsen; John A. Carucci (Clinical and Developmental Immunology)
Dendritic cells (DC) represent a diverse group of professional antigen-presenting cells that serve to link the innate and adaptive immune systems. Their capacity to initiate a robust and antigen-specific immune response has made them the ideal candidates for cancer immunotherapies. To date, the clinical impact of DC immunotherapy has been limited, which may, in part, be explained by the complex nature of DC biology. Multiple distinct subsets of DCs have been identified in the skin, where they can be broadly subcategorized into epidermal Langerhans cells (LC), myeloid-derived dermal dendritic cells (mDC) and plasmacytoid dendritic cells (pDC). Each subset is functionally unique and may activate alternate branches of the immune system. This may be relevant for the treatment of squamous cell carcinoma, where we have shown that the tumor microenvironment may preferentially suppress the activity of mDCs, while LCs remain potent stimulators of immunity. Here, we provide an in depth analysis of DC biology, with a particular focus on skin DCs and their role in cutaneous carcinoma. We further explore the current approaches to DC immunotherapy and provide evidence for the targeting of LCs as a promising new strategy in the treatment of skin cancer.